(untitled) (Revista de Ciências Agroveterinárias, 2007)
Aqueous extracts from green leaves of Nerium oleander L. and Dieffenbachia picta in concentrations of 0; 0,0625; 0,125 and 0,25 mg/mL were prepared with the objective of studying the allelopathic potential of these ornamental plant species on lettuce (test plant) and Bidens pilosa L seeds. The experiments were carried out in January of 2007, at the Genetic Laboratory of Santa Maria Federal University. The first count of germination (PCG), germination (G), germination speed index (IVG), root and shoot length, and fresh biomass (MF) were evaluated. Both species showed tendency to reduce the analyzed morphological variables from the concentration of 0,125 mg/mL. The seeds of Bidens pilosa L. were more sensible to aqueous extracts than lettuce seeds. The IVG showed the greatest reduction with the increase of extracts concentration. The MF of lettuce and Bidens pilosa L. plants were reduced from the concentration of 0,0625 mg/mL. Both extracts showed potential allelopathic activity.